Humanising economy: spirituality and sustainability for circular economy - Abdul Razak, Dzuljastri; Azam, Md Siddique E (ISTAC-IIUM, 2023)
This chapter discusses the concept of spirituality, spirituality in Islam and how it is significantly related to sustainability. A spiritually developed Muslim follows the do(s) and don’t(s) prescribed in Islam. Such practices of following halal and avoiding haram are referred to as adopting a halal lifestyle. Examples stated in the chapter show that the halal lifestyle develops a Muslim spiritually and significantly contributes toward sustainability. Additionally, the five objectives of Shariah are directly related to sustainability and sustainable development. In a nutshell, spirituality in Islam ensures sustainability in economic, social and environmental aspects of life while preserving the faith in religion.